2021
DOI: 10.1016/j.toxrep.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates exposure during pregnancy a study in a Mexican cohort

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…According to Li et al [22], phthalate metabolite concentrations throughout the pregnancy were U-shaped; the highest concentrations of phthalates were detected in the 1st and third trimesters. A similar trend to our study was observed in the study of Bustamante-Montes et al [23]; they noticed higher concentrations of MBP, MEP, and MEHP during the third trimester compared to the first trimester in the cohort of pregnant women. The possible explanation of higher exposure to certain phthalates during the third trimester might be a difference in caloric intake throughout the pregnancy.…”
Section: Biomonitoring Of Maternal Phthalate Metabolitessupporting
confidence: 92%
“…According to Li et al [22], phthalate metabolite concentrations throughout the pregnancy were U-shaped; the highest concentrations of phthalates were detected in the 1st and third trimesters. A similar trend to our study was observed in the study of Bustamante-Montes et al [23]; they noticed higher concentrations of MBP, MEP, and MEHP during the third trimester compared to the first trimester in the cohort of pregnant women. The possible explanation of higher exposure to certain phthalates during the third trimester might be a difference in caloric intake throughout the pregnancy.…”
Section: Biomonitoring Of Maternal Phthalate Metabolitessupporting
confidence: 92%
“…2019 ; James-Todd et al. 2017 ), by neighborhood ( Bustamante-Montes et al. 2021 ), and by education ( Zhu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Early life exposures to NMPs and plastics reflect numerous commercial and social determinants of health and are likely linked to health inequalities. Global inequalities in pregnant women's body burden of plastic chemicals has, for example, been reported by income (Wenzel et al 2018), by race/ethnic group (Bloom et al 2019;James-Todd et al 2017), by neighborhood (Bustamante-Montes et al 2021), and by education (Zhu et al 2016), among other socioeconomic factors. Some of this variation may reflect differences in proximity to pollution sources, dietary behaviors, occupational exposures, use of personal care products (Helm et al 2018;Zota and Shamasunder 2017), and intersections of these factors.…”
Section: Global Context Policy and Health Inequalitiesmentioning
confidence: 99%